Stuck on the Surface: Digitalization Case Studies of Three Local Televisions - Setiawan, Lukas Deni (Mediator: Jurnal Komunikasi, 2023)
This research examines television digitalization policies from the perspective of local television broadcasters. Local television has the potential to benefit in the context of digitalization. However, our excessive attention to the centrality of broadcasting continues to threaten the existence and progress of local television. This research uses a qualitative approach with in-depth interview data collection methods. The research informants were broadcasters of three local television stations: Jogja TV (Yogyakarta Special Region/DIY), Tegar TV (Lampung), and Lombok TV (West Nusa Tenggara/NTB), as well as one informant from the Indonesian Local Television Association (ATVLI) management. The results of this study indicate that since the beginning of the digitalization process, the government has not considered the perspectives of local television broadcasters in implementing broadcast digitalization. The fundamental issue of balancing the use of digital broadcasting infrastructure, such as multiplexing equipment, by various parties regarding digitalization still remains. As a result, the continued benefits of broadcast digitalization expected by local television broadcasters are still far from expectations. Therefore, local television broadcasters have not thought far enough to vary and improve the quality of their programs because they are still stuck on these basic problems.